Wildlife damage to crops: Perceptions of agricultural and wildlife leaders in 1957, 1987, and 2017 - Michael R. Conover; Erin Butikofer; Daniel J. Decker (Wildlife Society Bulletin)
ABSTRACT A national survey of wildlife agency directors was conducted during 1957 to determine their perceptions of wildlife damage to agriculture. This study was repeated in 1987, expanding the sample to include chief executive officers of state Farm Bureaus and state Wildlife Extension Specialists as well as wildlife agency leaders. During 2017, we replicated these studies to determine how perceptions of leaders had changed over the past 30 and 60 years. In the 2017 survey, 21 different wildlife species were reported by ≥1 respondent as causing the most damage in their state. Despite the numerous species causing damage, deer (Odocoileus spp.) were listed by most respondents as producing the most agricultural damage in their state. State Farm Bureaus and Wildlife Extension Specialists overestimated the amount of governmental services and products that were available to help farmers in their state. Most respondents believed that wildlife damage to agriculture was a serious problem in their state and had increased during the past 30 years. When survey results were compared, feral hog (Sus scrofa), goose (Anatidae), and wild turkey (Meleagris gallopavo) were listed more frequently in 2017 than in 1987, suggesting that problems caused by these species have increased in severity during the past 30 years. Use of special shooting and trapping permits issued to farmers had increased over the decades. Governmental agencies were more likely to provide fencing material and noisemakers and plant diversionary crops in 2017 and 1987 than they were in 1957. Modern wildlife management has been remarkably successful in increasing wildlife populations, to the point that some species occur in sufficient numbers in some places to cause remarkable levels of damage to crops and livestock. © 2018 The Wildlife Society.